Continuing education programme on vaccines for primary healthcare professionals: mixed-method protocol - Marina García-Gámez; María González-Cano-Caballero; Eloísa Fernández-Fernández; Eloísa Fernández-Ordoñez; María Dolores Cano-Caballero; Cristina Guerra-Marmolejo (BMJ Open, 2022)
Introduction Vaccination is a fundamental intervention in disease prevention; therefore, the advice and recommendations of health professionals have a major influence on the population’s decision to be vaccinated or not. Professionals must have sufficient competencies to carry out their work and recommend vaccination with evidence-based knowledge. The aim is to design and validate a strategy to improve professional competencies in vaccination to positively influence adherence and increase vaccination rates in the population.Methods and analysis Training will be designed based on evidence and previous studies and piloted with healthcare providers. To test changes in knowledge, a pretest and post-test will be conducted. To test feasibility, a think-aloud method will be used with participants and triangulated with focus groups using SWOT (strengths, weaknesses, opportunities and threats) analysis. Transfer will be measured using the questionnaire ‘factors for the indirect evaluation of transfer’ and an efficacy questionnaire 1½ months later; for satisfaction, an ad hoc questionnaire will be used. A summative approach will be used for the analysis of the focus groups and descriptive and bivariate statistics for the questionnaires.Ethics and dissemination This study was approved by the Andalusian Research Ethics Committee, Spain (approval number: 0524-N-20). The results will be made available to the public at journal publications and scientific conferences.